Results of artificial reproduction of sturgeons reared in cages with natural temperature regime of water bodies of the forest-steppe zone of Ukraine - M. Pashko; A. Tretiak; S. Pashko; Y. Kolos; N. Mykhaylenko (Ribogospodarsʹka Nauka Ukraïni, 2018)
Purpose. To determine main the technological parameters of artificial reproduction of sterlet (Аcipenser ruthenus) and Siberian sturgeon (Acipenser baerii) with a combined use of industrial aquaculture methods.